Evaluation of the Queue Information System at Disdukcapil Prabumulih City Using the COBIT 5 Framework - Evi Anisyah; Fajriyah; Dili Muhammad P; Krisna; Reza Ananda P (NEXCORE: Journal of Computer Science & Intelligent Systems, 2026)
This study aims to analyze and evaluate the queue service information system at the Department of Population and Civil Registration (Disdukcapil) of Prabumulih City using the COBIT 5 framework. The background of this research lies in the need to improve efficiency and the quality of public services through a reliable information system. The research method employed is descriptive with a case study approach. Data were collected through surveys and interviews, then analyzed using relevant COBIT 5 domains. The findings reveal several weaknesses in the existing queue system, such as issues of reliability and efficiency. Based on these results, several improvement measures are recommended to enhance the performance and service quality of Disdukcapil. The conclusion emphasizes the importance of applying COBIT 5 in auditing and managing information systems for public service delivery.